ChemInform Abstract: Iron‐ and Indium‐Catalyzed Reactions Toward Nitrogen‐ and Oxygen‐Containing Saturated Heterocycles. Issue 21 (May 2015) - Cornil, Johan; Gonnard, Laurine; Bensoussan, Charlelie; Serra‐Muns, Anna; Gnamm, Christian; Commandeur, Claude; Commandeur, Malgorzata; Reymond, Sebastien; Guerinot, Amandine; Cossy, Janine
Abstract Review: 74 refs.